Forebrain neuroanatomy of the neonatal and juvenile dolphin (T. truncatus and S. coeruloalba) - Parolisi, Roberta; Peruffo, Antonella; Messina, Silvia; Panin, Mattia; Montelli, Stefano; Giurisato, Maristella; Cozzi, Bruno; Bonfanti, Luca (Frontiers in Neuroanatomy, 2015)
Knowledge of dolphin functional neuroanatomy mostly derives from post-mortem studies and non-invasive approaches (i.e., magnetic resonance imaging), due to limitations in experimentation on cetaceans. As a consequence the availability of well-preserved tissues for histology is scarce, and detailed histological analyses are referred mainly to adults. Here we studied the neonatal/juvenile brain in two species of dolphins, the bottlenose dolphin (Tursiops truncatus) and the striped dolphin (Stenella coeruleoalba), with special reference to forebrain regions. We analyzed cell density in subcortical nuclei, white/gray matter ratio, and myelination in selected regions at different anterior–posterior levels of the whole dolphin brain at different ages, to better define forebrain neuroanatomy and the developmental stage of the dolphin brain around birth. The analyses were extended to the periventricular germinal layer and the cerebellum, whose delayed genesis of the granule cell layer is a hallmark of postnatal development in the mammalian nervous system. Our results establish an atlas of the young dolphin forebrain and, on the basis of occurrence/absence of delayed neurogenic layers, confirm the stage of advanced brain maturation in these animals with respect to most terrestrial mammals.